Autoafhankelijkheid en kansarmoede in Brussel - Mathias De Meyer; Jessica Gilsoul (Brussels Studies)
In this article, we address the intersecting issues of deprivation and car dependency in the Brussels Region by analysing the car ownership of households through the prism of their level of deprivation. In order to do this, we have used the “Survey on Income and Living Conditions” (SILC). We have thus constructed a typology of households defined according to the trade-offs they have made between the costs and benefits of car ownership. We focus in particular on the socioeconomic characteristics of households with cars in situations of deprivation. On this basis, we are able to assess the economic stress on household budgets caused by car ownership and put forward hypotheses regarding the professional and household configurations which imply a high level of car dependency, even in an urbanised setting such as that of the Brussels Region.